Dielectric Properties of Lunar Subsurface Materials. Issue 22 (19th November 2020) - Dong, Zehua; Fang, Guangyou; Zhao, Di; Zhou, Bin; Gao, Yunze; Ji, Yicai
Abstract: The dielectric permittivity is one of the most significant properties of lunar material. For the past decades, researchers have assumed or used an indirect density versus depth relation to constrain the subsurface permittivity on the Moon. On 3 January 2019, Chang'E‐4 (CE‐4) rover‐borne lunar penetrating radar (LPR) successfully landed on the Von Kármán crater on the Moon's farside. CE‐4 LPR is the first surface radar on the Moon's farside for exploring regolith thickness and geological structure. Numerous parabolic‐shaped diffractions (PSD), which indicate subsurface objects, are identified in LPR data. We estimate the permittivity of the first ~50 m at the landing region using these PSDs based on a hyperbolic fitting method. A best‐fit permittivity/density versus depth relation is obtained, and this relation could be used at different areas on the Moon. Plain Language Summary: Currently, rover‐deployed/spaceborne radar systems are frequently employed in lunar exploration. The depth and thickness of lunar subsurface structure observed from radar data are completely influenced by the dielectric properties of subsurface materials. The dielectric properties also provide vital clues on compositions and origin of subsurface materials. However, except the results measured with returned sample from lunar surface, we have no more information about dielectric properties of global and deeper lunar subsurface materials. In January, China's CE‐4 spacecraft softly landed on the farside of the Moon for the first time and released the lunar penetrating radar (LPR). In this study, we estimate the dielectric permittivity of the first ~50 m at the landing region with LPR data and propose a best‐fit permittivity/density versus depth relation which could be used at different areas on the Moon. Key Points: The permittivity of lunar subsurface materials at CE‐4 landing site is estimated A best‐fit permittivity/density versus depth relation is obtained The obtained best‐fit relation can be used at different areas on the Moon